Parenting Styles and Academic Self-Efficacy Beliefs of Omani School and University Students - Said S. Aldhafri; Marwa N. Alrajhi; Hussain A. Alkharusi; Ibrahim S. Al-Harthy; Hafidha S. Al-Barashdi; Amal S. Alhadabi (MDPI AG, 2020)
The present study examined the predictive role of students' perceptions of parenting styles on their academic efficacy beliefs. This relationship was examined using two large sets of national data that were collected from school and university students to see how the relationship between parenting styles and academic efficacy beliefs may or may not vary across life stages. The sample included 1431 school students and 1119 university students cross the Sultanate of Oman. The participants responded to the Arabic version of the Parental Authority Questionnaire (PAQ) and to the Academic Self-Efficacy Scale (ASES) constructed by the researchers. Using linear regression model for each sample, the results showed that the amount of variance in school students' academic self-efficacy beliefs explained by parenting styles (R2 adjusted = 0.21) was higher than the amount of variance explained for the university sample (R2 adjusted = 0.10). The researchers concluded that the effects of parenting styles on students' self-efficacy beliefs decrease as children grow up.